vremigi
contestada

50 points!!!

A system of equations is shown below:


6x − 2y = 3 (equation 1)

5x + 3y = 4 (equation 2)


A student wants to prove that if equation 2 is kept unchanged and equation 1 is replaced with the sum of equation 1 and a multiple of equation 2, the solution to the new system of equations is the same as the solution to the original system of equations. If equation 2 is multiplied by 1, which of the following steps should the student use for the proof?




Show that the solution to the system of equations 10x + y = 7 and 5x + 3y = 4 is the same as the solution to the given system of equations

Show that the solution to the system of equations 10x − 2y = 7 and 5x + 3y = 4 is the same as the solution to the given system of equations

Show that the solution to the system of equations 11x − y = 7 and 5x + 3y = 4 is the same as the solution to the given system of equations

Show that the solution to the system of equations 11x + y = 7 and 5x + 3y = 4 is the same as the solution to the given system of equations

Respuesta :

The student wants to prove they are the same by adding the two systems together, and keeping the second equation the same. 

So add these two:

6x - 2y = 3
5x + 3y = 4
11x + y = 7

So the answer will be the last choice:

Show that the solution to the system of equations 11x + y = 7 and 5x + 3y = 4 is the same as the solution to the given system of equations

THE ANSWER IS THE LAST ONE

The student wants to prove they are the same by adding the two systems together, and keeping the second equation the same. 


So add these two:


6x - 2y = 3

5x + 3y = 4

11x + y = 7